Xinqin exhibits the anti-allergic effect through the JAK2/STAT5 signaling pathway. (4th December 2016) - Zhang, Qian; Xiong, Ying; Li, Guo-Bing; Tang, Qin; Cao, Min; Huang, Jing-Bin; Xing, Mao; Hu, Chang-Peng; Gong, Ya; Wang, Qing-Hua; Gao, Ning; Zhang, Rong
Abstract: Ethnopharmacological relevance: Xinqin, a polyherbal medicine, is an important traditional Chinese herbal formula used in traditional oriental medicine for treatment of allergic rhinitis (AR). The formula is based on the Chinese Pharmacopoeia Aim of the study: Previously, Xinqin exhibited potent anti-allergic effect in a guinea pig model of AR. In this study, we explored the molecular mechanism of the anti-allergic effect mediated by Xinqin. Materials and methods: AR was induced in guinea pigs (Hartley) with toluene-2, 4-diisocyanate (TDI) in vivo and in HMC-1 mast cells with A23187/phorbol 12-myristate-13-acetate (PMA) in vitro. The releases of allergic inflammatory mediators such as histamine, leukotriene (LT) D4, immunoglobulin (Ig) E, TNF-α, and IL-6 were analyzed for allergy. The mast cell degranulation was displayed in HMC-1 mast cells. The activities of janus protein kinase 2 (JAK2), signal transduction and activator of transcription 5 (STAT5) and suppressor of cytokine signaling 3 (SOCS3) were evaluated by Western blot. Results: Treatment with Xinqin resulted in AR symptoms and decreases in levels of histamine, LTD4, IgE, TNF-α, and IL-6 in serum of guinea pig model of AR and in A23187/PMA-stimulated HMC-1 mast cells. Treatment with Xinqin also inhibited cell degranulation in A23187/PMA-stimulated HMC-1 mast cells. The JAK2/STAT5 signaling pathway could play an important role in the anti-allergic activity mediated by Xinqin. Conclusions: Xinqin exerts the anti-allergic effect by modulating mast cell-mediated allergic responses by down-regulating JAK2/STAT5 signaling pathway. Results from this study provide a mechanistic basis for the application of Xinqin in the treatment of AR. Graphical abstract: